Advance Demand Information as a Tool for Value Chain Planning of Biofortified Foods in Brazil - Voese, Simone Bernardes; Espejo, Marcia Maria dos Santos Bortolocci; Planells, Mariana (Journal of Agricultural Studies, 2021)
Biofortified foods represent an alternative to minimize extreme and “hidden” hunger in people. Aiming to look at this sector as a business, this study seeks to identify potential demand in the consumer market regarding fortified foods in Brazil. In order to do these, multiple sources of data collection were adopted to access different markets for these products. In the first part of the research a survey of Brazilian government programs was carried out, which could encourage the demand of biofortified foods. In addition a conversation was undertaken with stakeholders seeking to identify the perception of agents who take part in the value chain, which included the project developer in Brazil (Embrapa) to the food industry. Additionally a quantitative research was carried out using Mann-Witney and Chi-square tests, and also Multiple Correspondence Analysis, aiming to evaluate the perception of final consumers regarding biofortified foods. Looking at the results a potential demand was identified for biofortified foods, through government programs as well as via the food industry, despite needing larger promotion amongst the Brazilian population, as the sample showed a considerable lack of awareness. In relation to biofortified foods each market showed different interests, such as Cascavel, Parana, which showed greater interst in School Meals with corn and cassava. While in the food industry the interest was more considerable for sweet potato, and amongst the final consumers there was a bigger interest in corn and beans. A potential demand in several markets for all biofortified foods was also shown.